2018
DOI: 10.1007/s40003-018-0320-z
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Dynamics of Perilla Leaves in a Hill Farming System

Abstract: Decomposition dynamics and N and P release from Perilla frutescence were assessed for suitability of its leaves to reincorporate into cropping systems for nutrient enrichment in the Indian Himalayan Region. Nitrogen concentration was greater in the green leaves of Perilla sp. and phosphorous in the freshly fallen leaf litter. Lignin concentration varied between 11.95 and 26.94% and registered an increase trend across altitudinal gradient. Decay pattern of Perilla leaf litter was similar at three different alti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…The lower decay rate of the species might be due to higher lignin, lignin/P and phenolic content. Similar study showed that although the nitrogen content was higher, Sharma et al (2018) reported lignin as the limiting factor for lower decay rate of Perilla leaf litter.…”
Section: O N L I N E C O P Ysupporting
confidence: 55%
“…The lower decay rate of the species might be due to higher lignin, lignin/P and phenolic content. Similar study showed that although the nitrogen content was higher, Sharma et al (2018) reported lignin as the limiting factor for lower decay rate of Perilla leaf litter.…”
Section: O N L I N E C O P Ysupporting
confidence: 55%